Anthropometric and Ergonomic approach to the ageing: the importance of the multidisciplinary study in the act on ageing project (Piedmont region) (Journal of Biological Research - Bollettino della Società Italiana di Biologia Sperimentale, 2012)
-
Keywords: ageing; anthropometric analysis; home hazards